Investigation on the Effect of the Shaft Transition Form on the Inflow Pattern and Hydrodynamic Characteristics of the Pre-Shaft Tubular Pump Device - Luo, Can; Du, Kang; Qi, Weijun; Cheng, Li; Huang, Xianbei; Lu, Jiaxing (Frontiers in Energy Research, 2022)
The shaft tubular pump device is widely used in low head pumping stations in plain areas. The N-S equation and the SST k-ω turbulence model are adopted. Then, the investigation on the influence of the shaft transition form on the inflow pattern and hydrodynamic characteristics of the pre-shaft tubular pump device is carried out. By designing three transition forms of shafts, different inflow patterns are provided for the tubular pump device. The characteristic parameters of the shafts and external and internal flow characteristics of the pumping device under different inflow patterns are compared and analyzed. Finally, the optimal transition form is selected for model tests, and unsteady pressure pulsation characteristics are studied. The results show that the flow pattern in the inlet passage of each case is relatively uniform and smooth, and the range of the high-efficiency zone of the pump device is roughly within 0.9Qd–1.2Qd. The energy loss and the weighted average angle on the outlet of each case are similar. The axial velocity distribution uniformity on the impeller inlet of case 1 is better than that of the other cases. The numerical simulation results are consistent with the experimental results, and the numerical simulation method is reliable. Under the design condition, the pressure pulsation amplitude at the impeller inlet is the largest. It gradually increases from the hub to the shroud. The main frequency of pressure pulsation is the blade frequency. The pressure pulsation amplitude at the impeller outlet decreases from the hub to the shroud. The main frequency is not constant due to the rotor–stator interaction between the impeller and the guide vane. The outcome will be beneficial to the design and optimization of the shaft tubular pump device, which is helpful for broadening the corresponding theory and applying it to the actual project.